Economics and Agronomics of Relay‐Cropping Pennycress and Camelina with Soybean in Minnesota. (1st May 2019) - Ott, Matthew A.; Eberle, Carrie A.; Thom, Matt D.; Archer, David W.; Forcella, Frank; Gesch, Russell W.; Wyse, Donald L.
Abstract : Core Ideas: Net income from relay cropping was rarely different from that of mono‐cropping. A 25‐cm oilseed row spacing was likely too narrow for optimal soybean growth. Further domestication of oilseeds will likely improve relay cropping with soybean. ABSTRACT: Cover crops can serve as a valuable management tool for improving soil and water quality, but are an added expense for farmers. We evaluated the yields and economics of four cover crops and two winter fallow treatments in a spring wheat ( Triticum aestivum L.)–soybean [ Glycine max (L.) Merr.] rotation at three sites in Minnesota. The four cover crop treatments were winter rye ( Secale cereal L.), forage radish ( Raphanus sativus L.), winter camelina [ Camelina sativa (L.) Crantz], and pennycress ( Thlaspi arvense L.) planted into spring wheat stubble. The fallow treatments consisted of no‐tilled and conventionally tilled soil. Radish winterkilled and rye was terminated chemically before planting soybean in early May. Soybean was inter‐seeded between rows of camelina and pennycress at the same time it was planted in other treatments. Camelina and pennycress were harvested over soybean seedlings in late June. Camelina yields ranged from 600 to 1100 kg ha −1, while pennycress ranged from 900 to 1550 kg ha −1 . Mono‐cropped soybean averaged 1819, 3510, and 4180 kg ha −1 in northern, central, and southern Minnesota, respectively. Soybean seedlings under oilseed cover crop canopies exhibited light‐stress, which likely reduced soybean yield in these treatments by 22 to 30%. When oilseed and inter‐seeded soybean yields were combined, total seed yields generally were equal to or exceeded those of mono‐cropped soybean. In addition, net income for inter‐seeded systems was typically equivalent to mono‐cropped soybean. Improvements in net income are likely needed before the benefits of oilseed cover crops are fully realized.